2020
DOI: 10.1093/cid/ciaa422
|View full text |Cite|
|
Sign up to set email alerts
|

Population Movement, City Closure in Wuhan, and Geographical Expansion of the COVID-19 Infection in China in January 2020

Abstract: Background The unprecedented outbreak of 2019-nCoV pneumonia infection in Wuhan City caused global concern, the outflowing population from Wuhan was believed to be a main reason for the rapid and large-scale spread of the disease, so the government implemented a city closure measure to prevent its transmission considering the large amount of travelling before the Chinese New Year.Methods Based on the daily reported new cases and the population movement data between January 1 and 31, we examined the effects of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 22 publications
0
51
0
Order By: Relevance
“…The joint distribution between weather and potential confounders should be taken into account. For example, population movement might trigger the transmission of COVID-19 [45]. As for the effects of interventions, we have plotted the time series of temperatures from January 24, 2020 to February 13, 2020 in Beijing, Shanghai, Guangzhou, and Chengdu in Additional file 1: Figure S1.…”
Section: Effects Of Temperature and Humidity On The Transmission Of Cmentioning
confidence: 99%
“…The joint distribution between weather and potential confounders should be taken into account. For example, population movement might trigger the transmission of COVID-19 [45]. As for the effects of interventions, we have plotted the time series of temperatures from January 24, 2020 to February 13, 2020 in Beijing, Shanghai, Guangzhou, and Chengdu in Additional file 1: Figure S1.…”
Section: Effects Of Temperature and Humidity On The Transmission Of Cmentioning
confidence: 99%
“…3 The COVID-19 outbreak caused a sudden, significant increase in hospital visits from infected and suspected individuals over the course of two months. [4][5][6] The large patient surge overwhelmed hospitals, despite continuous efforts to expand hospital capacity. Hospital waiting times were extended, which increased the time before infected individuals were identified and placed into isolation.…”
Section: Introductionmentioning
confidence: 99%
“…Descriptive modeling research that leverages this capability has examined the spatial associations of COVID-19 with socioeconomic and environmental characteristics. This research found, for example, that lower income and income inequality (22), higher temperature and humidity (23), exposure to fine particulate air pollution (24), and mobility and transportation (25,26) were associated with a higher prevalence of COVID-19 cases or mortality. GIS&T also offers approaches to investigating statistical spatial effects and spatial heterogeneity, such as spatial autoregressive models and geographically weighted regression, to account for modeling geographic processes such as spatial diffusion and the variation in relationships among variables over space (27,28).…”
Section: Integrating Geographic Data In Covid-19 Modelingmentioning
confidence: 88%